Peningkatan Kompetensi Guru SD Melalui Workshop Media Belajar Interaktif Menggunakan Assemblr Edu dan Artificial Intelligence - Fawwaz, Muhammad Iqbal; Akbar, Muhammad Fikri; Churiyah, Madziatul; Sholikhan, Sholikhan (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2024)
Digitalisation in Indonesia has seen a significant development in education in recent years. Nevertheless, issues persist in the educational journey, including the absence of interactive and creative learning tools in primary education institutions. Teachers, at the forefront of the educational journey, hold a vital role in crafting learning materials. In the field, particularly in Gugus 5 Blimbing, it is evident that numerous educators lack the skills to create engaging and inventive learning resources. Consequently, student engagement and motivation suffer, resulting in a less impactful learning experience. To address this issue, a workshop focused on creating user-friendly learning materials, accessible to all educators, is essential. Assemblr Edu offers a platform for educational institutions to generate interactive 3D learning tools using Augmented Reality (AR).  Educational establishments have the ability to enhance learning materials by implementing Augmented Reality technology, allowing students to view virtual objects within the classroom.  The target output of this activity is that driving school teachers in Gugus 5 Blimbing have competence in developing 3D interactive learning media using Assemblr Edu Augmented Reality and AI technology.